Implementing the Extractive Industries Transparency Initiative : Applying Early Lessons from the Field - World Bank (The World Bank, 2008)
The Extractive Industries Transparency Initiative (EITI) was established as a global initiative in 2002. The EITI has since become the highest profile international standard for promoting transparency and accountability in countries dependent on oil, gas, minerals, and metals. As it is built around cooperation among governments, companies, and civil society organizations, the EITI has been called a "curious coalition" by some. However, this coalition now helps drive transparency in revenues and payments in resource-rich countries across the world as part of their good governance programs